Essentials of septorhinoplasty : philosophy-approaches-techniques - Behrbohm, Hans; Tardy, M. Eugene, Jr., 1934-; Behrbohm, Wibke (Noida : Thieme, 2017)
"Essentials of Septorhinoplasty: Philosophy-Approaches-Techniques, Second Edition, integrates the functional and aesthetic aspects of complex nasal surgery to address both cosmetic and breathing issues that often occur simultaneously. Fully revised and updated, this new edition covers surgery of the septum, open rhinoplasty techniques, and closed endonasal techniques, as well as anatomy, diagnosis and preoperative planning, patient psychology, postoperative treatment, and potential complications. Illustrations detailing surgical steps and before-and-after photographs to help plan procedures make this book a complete and practical guide to septorhinoplasty. Features: New and expanded discussion of biostatic surgery, submucosal septal surgery, radiofrequency surgery, endoscopic procedures, DCF implants, and more. Step-by-step description of operative procedures, including the latest graft and suture techniques. More than 600 exquisite illustrations and high-quality color photographs that enhance the text. Contributions from renowned names in the fields of otolaryngology and facial plastic surgery. Essentials of Septorhinoplasty: Philosophy-Approaches-Techniques, Second Edition, is the only book of its kind to incorporate functional and aesthetic considerations in nasal surgery. It is a beneficial addition to the library of any otolaryngologist, facial plastic surgeon, and maxillofacial surgeon who aims to improve both form and function of the nose"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nose -- Surgery; Nasal Septum -- surgery; Rhinoplasty -- methods